The Effect of External Audit Quality, Auditor Reputation, and Auditor Rotation on the Financial Performance of Conventional Banks in Indonesia - Ni Nyoman Nikunja Vasini; Dewi Susilowati (Ilomata International Journal of Tax and Accounting, 2026)
This study examines the impact of external audit quality, auditor reputation, and auditor rotation on the financial performance of conventional banks in Indonesia. A panel data regression approach is applied to a sample of 28 conventional banks listed on the Indonesia Stock Exchange from 2020 to 2024, yielding 140 bank-year observations, and a Random Effects Model is used as the estimator. Bank financial performance is proxied by return on investment (ROI), measured as net profit after tax divided by total earning assets, as these assets represent the primary source of bank income and reflect the effectiveness of core banking asset management. External audit quality is proxied by the number of OJK-licensed Public Accountants within a Public Accounting Firm; auditor reputation is measured by the auditor’s sanction history; and auditor rotation is defined as changes in Public Accountants within the same firm.  The results show that external audit quality is positively associated with bank financial performance ( = 0.0016), while auditor reputation is also positively associated ( = 0.0012). In contrast, auditor rotation shows a negative association ( = -0.0019). The strongest positive coefficient is found in external audit quality, whereas auditor rotation shows the strongest effect in absolute magnitude. These findings support Agency Theory by emphasizing the role of external auditing as a monitoring mechanism to reduce information asymmetry. This study contributes methodologically by introducing auditor-level proxies within the OJK regulatory framework and offers practical implications for regulators and Public Accounting Firms in strengthening supervisory effectiveness in the banking sector.